Konseling Sebaya dalam Memberdayakan Anak Jalanan Berbasis Masjid (Inkorporasi Perspektif Anak Jalanan Berbasis Komunitas Melalui Pendekatan Participatory Action Research) - Muhammad Husni (LP2M UIN Sunan Kalijaga, 2017)
Empowering street children is a form of care and attention toward their lives as they are also children of the nation who have the rights to live a decent life. The empowerment of street children attempts to get them off the streets and turn them into becoming more independent with pride and dignity as human being. Street children are a part of the marginalized community requiring supervision, which is not easy to do as there are negative stigmas or impressions in the community regarding their presence, and unsupportive family environment. These two stigmas will be incessant unless individual street children changes themselves to escape from the community of street children. The target of this activity is to change the mindset of street children. From a negative way of thinking to a positive one, from bad to good. Some of the efforts undertaken in accomplishing that, among others, are by holding activities of religious discussions, group prayers, and getting in the habit of gathering in prayer rooms (musala). These three activities have been carried out maximally. The second target of this activity is enhancing the children’s skills. The efforts carried out were activities for developing electrical skills, culinary skills, calligraphy, and alternative medicine of wet cupping. The entire process of these activities ran well and properly within a period of 2 months by providing close assistance and supervision. The third target aims at developing an entrepreneurial spirit and a spirit of self-appreciation throughout all aspects of life. In this case, the achievement expected of the street children is for them to develop awareness and desire to establish business endeavors that will be beneficial to themselves.[Pemberdayaan anak jalanan sebagai wujud kepedulian terhadap nasib anak jalanan, juga merupakan anak bangsa yang berhak memperoleh kehidupan yang layak. Pemberdayaan anak jalanan berupaya pengentasan anak jalanan dari jalanan dan menjadikan mereka mandiri serta mempunyai harkat dan martabat sebagai manusia. Anak jalanan bagian dari komunitas marjinal yang memperlukan pembinaan, tidak mudah untuk melakukannya karena stigma atau kesan negative dari masyarakat tentang keberadaan mereka, dan lingkungan keluarga yang kurang mendukung. Dua stigma itu tidak dapat dihilangkan terkecuali individu anak jalanan merubah dirinya untuk keluar dari komunitas anak jalan.Target kegiatan ini merubah mindset anak jalanan. Cara berfikir yang negative menjadi positif, buruk menjadi baik. Beberapa upaya yang dilakukan dalam merubah itu di antaranya kegiatan diskusi keagamaan, salat berjamaah, dan membiasakan diri untuk kumpul di musala. Tiga kegiatan ini sudah dijalankan secara maksimal.Target yang kedua dalam kegiatan ini mengembangkan keterampilan anak. Upaya yang dilakukan adalah keterampilan elektro, keterampilan boga, kaligarfi dan pengobatan alternatif bekam. Secara keseluruhan proses kegiatan ini dapat berjalan dengan lancar dan baik dalam jangka waktu 2 bulan pendampinganTarget ke tiga, menumbuhkan jiwa kewirausahaan. Semangat untuk mengapresasikan diri dalam segala sisi kehidupan. Dalam hal ini, pencapaian yang diharapkan tumbuh kesadaran bagi peserta dampingan keinginn untuk mengembangkan usaha yang dapat bermanfaat bagi dirinya.]